Urban impact on water bodies in the Luleå area, northern Sweden - Rentz, Ralf (Luleå tekniska universitet, Geovetenskap och miljöteknik, 2008)
Anthropogenic activities change the quality of urban waters and sediments. The aim of this study was to describe and quantify pollution from different point sources in Luleå, northern Sweden. In the first article, sediment samples and porewater of an enclosed bay (Skutviken) near the centre of Luleå affected by stormwater discharge were analyzed for major and trace elements and 16 polycyclic aromatic hydrocarbons (PAHs), and compared with a reference site. Cadmium, Cu, Pb, and Zn were enriched at Skutviken. Also the PAH content was enriched, in particular for phenantrene, anthracene, fluoranthene, and pyrene, which are common constituents in stormwater. The use of trace metal ratios provided indications about pollutant sources. Pb-210 dating was used to determine historical changes in metal and PAH fixation in the sediment. The bay Skutviken is enclosed through the construction of a road bank since 1962. The enclosure caused reduced water circulation in the bay, which promotes the occurrence of anoxic conditions with sulphate reduction within the bay. As a consequence of these conditions, metals are trapped in the sediments as sulphides. This study suggests that urban pollutants are efficiently trapped in enclosed bays with restricted water circulation. Such bays are common in areas with postglacial land uplift, where enclosures may have an important impact on water and sediment qualities. The second article describes the conditions in several water bodies close to Luleå. The various catchment areas affect the water and sediment quality of neighbouring and partially connected water bodies on a local level. Point sources, such as a steel plant, stormwater and petrol filling stations were accounted for their impact on water and sediment quality. Postglacial land uplift implies continuous changes of the environment. The natural premises concede possibilities of trapping pollutants in the water bodies. However, in the long term land uplift may also imply the release of trapped pollutants if the submerged soils ...